EMPLOYEE JOB SATISFACTION AT THE SKPD OFFICE OF THE WATER RESOURCES MANAGEMENT SERVICE OF SIDENRENG RAPPANG REGENCY - Indah Munis; A. Kartini Sari Putri D; Dian Nirmasari; Gazali Amin (Paser Institute Management and Busines, 2024)
Every organization, whether it's a business, social, or government organization, aspires to achieve a specific goal. The goal of an organization can be achieved through the effective and efficient use of human resources and other organizational resources, such as funds, materials, and equipment. Human Resources is an important element of organizations and plays a key role in the activities carried out by the organization. It is also the primary asset of an organization, which can determine the success or failure of the organization's mission and vision. This research aims to examine the effect of work status on employee job satisfaction at PSDA Office SKPD. The research use a quantitative method with Likert scale a sample size of 46 respondents. Data collected for this study was collected using a questionnaire, and processed by SPSS version 21. The sampling technique used was non-probability sampling. Simple linear regression analysis was used to analyze the data, and statistical techniques were applied to test for validity and reliability. The results of the test showed that work status a significant positive effect on employee job satisfaction at Sidenreng Rappang.